Tricuspid valve disease: diagnosis, prognosis and management of a rapidly evolving field - Asmarats, Lluis; Taramasso, Maurizio; Rodés-Cabau, Josep (Nature reviews cardiology, 2019)
Tricuspid valve disease, and particularly tricuspid regurgitation, is a highly prevalent condition with a complex pathophysiology and long-term adverse consequences. Although historically neglected, tricuspid valve disease has gained increasing recognition, with important advances in the assessment and management of this disorder over the past 2 decades. Surgical treatment remains the standard of care, but it continues to have one of the the highest death rates among all cardiac valve-related procedures, and a broad range of patients still do not receive effective therapy for tricuspid valve disease in contemporary clinical practice. Therefore, several alternative, less-invasive technologies for treating patients with severe, native tricuspid valve disease at high surgical risk have been developed in the past decade, with promising early results. This Review summarizes key findings and highlights the latest developments in the diagnosis and management framework that are transforming clinical practice in the complex field of tricuspid valve disease.